FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS QUALITY PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI - Widjaja, Nehemia Davis; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study was to examine and obtain empirical evidence regarding factors of earnings quality which includes the influence of leverage, liquidity, and firm size. The research was conducted in manufacturing companies sector consumer goods listed in the Indonesian Stock Exchange during the 2019-2021 period. This research used 23 manufacturing companies in the consumer goods sector as a sample after selected by purposive sampling method. This research processed using EViews 12 software and using multiple linear regression analysis techniques to test the hypothesis. Based on this research, the results shows that leverage and liquidity have positive effect toward earnings quality, meanwhile firm size has no effect towards earnings quality.